2018
DOI: 10.1183/13993003.01817-2017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and inflammatory phenotyping by breathomics in chronic airway diseases irrespective of the diagnostic label

Abstract: Asthma and chronic obstructive pulmonary disease (COPD) are complex and overlapping diseases that include inflammatory phenotypes. Novel anti-eosinophilic/anti-neutrophilic strategies demand rapid inflammatory phenotyping, which might be accessible from exhaled breath.Our objective was to capture clinical/inflammatory phenotypes in patients with chronic airway disease using an electronic nose (eNose) in a training and validation set.This was a multicentre cross-sectional study in which exhaled breath from asth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(139 citation statements)
references
References 48 publications
1
138
0
Order By: Relevance
“…In addition, we did not include lung imaging, such as CT scan findings, another modality for measuring COPD severity. [17] Finally, while this does not include exhaled breathomics, [18] this extraction tool could be used to assist recruitment for COPD patients into subsequent studies, with potential candidates identified according to severity of FEV1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we did not include lung imaging, such as CT scan findings, another modality for measuring COPD severity. [17] Finally, while this does not include exhaled breathomics, [18] this extraction tool could be used to assist recruitment for COPD patients into subsequent studies, with potential candidates identified according to severity of FEV1.…”
Section: Discussionmentioning
confidence: 99%
“…Exhaled breath analysis was carried out in duplicate with a 2-minute interval by eNose technology (SpiroNose) on the same day as the spirometry tests. The SpiroNose is a technically and clinically validated integration between routine spirometry and eNose technology, allowing stratification of patients in the doctor's office [12,14]. The SpiroNose has seven cross-reactive metal-oxide semiconductor sensors (sensors 1-7) for in duplicate sampling of exhaled air and the same set of sensors sampling ambient air for background correction (supplementary Figure S1 and Table S1, available at Annals of Oncology online).…”
Section: Measurementsmentioning
confidence: 99%
“…The SpiroNose has seven cross-reactive metal-oxide semiconductor sensors (sensors 1-7) for in duplicate sampling of exhaled air and the same set of sensors sampling ambient air for background correction (supplementary Figure S1 and Table S1, available at Annals of Oncology online). From each sensor signal, two variables are determined: (i) the highest sensor peak normalized to the most stable sensor, sensor 2, to minimize interarray differences and (ii) the ratio between the sensor peak and the breath hold (BH) point [14]. A detailed description of the measurement, set-up and the everyday verification of the sensor stability is included in the supplementary material, available at Annals of Oncology online.…”
Section: Measurementsmentioning
confidence: 99%
See 2 more Smart Citations